2002
DOI: 10.1081/jdi-120013968
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Hepatitis C Virus Infection in Hemodialysis Units: Effect of Isolation?

Abstract: Hepatitis C virus (HCV) infection has recently become the major cause of chronic liver disease among patients on chronic hemodialysis. The use of erythropoietin for treatment of anemia has reduced the number of blood transfusions, but the frequency of HCV infection has not declined in hemodialysis units. The exact mode of transmission of HCV within dialysis units is as yet incompletely defined, but there is evidence to support nosocomial transmission by sharing dialysis machines in the hemodialysis unit. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Due to the risk of transmission of hepatitis in the many dialysis centers around the world, dialysis machines used by patients with hepatitis, and even their rooms, are separated from other patients (14,15). However, no such separation of endoscopy devices, which are in direct contact with patient blood and secretions, is undertaken, even though such equipment may, in fact, have a higher risk of transmission than dialysis machines.…”
Section: Ankara üNiversitesi Tıp Fakültesi Mecmuası 2011 64(3)mentioning
confidence: 99%
“…Due to the risk of transmission of hepatitis in the many dialysis centers around the world, dialysis machines used by patients with hepatitis, and even their rooms, are separated from other patients (14,15). However, no such separation of endoscopy devices, which are in direct contact with patient blood and secretions, is undertaken, even though such equipment may, in fact, have a higher risk of transmission than dialysis machines.…”
Section: Ankara üNiversitesi Tıp Fakültesi Mecmuası 2011 64(3)mentioning
confidence: 99%
“…Lack of strict adherence to universal precautions by staff and sharing of articles such as multidose drugs might be the main mode of nosocomial HCV spread among HD patients [31, 65, 147, 149, 150,152,153,154]. Although some studies found that nosocomial spread of HCV declined when HCV-infected patients were treated in dedicated HD units [12,13,14,15,16,17, 41, 155], other investigators could control nosocomial spread of HCV among HD patients by strict application of hygienic precautions without isolation of HCV-infected subjects or machine segregation [56, 152, 156]. Indeed, the presented efficacy of segregation policy and use of dedicated units for HCV-infected patients might be simply due to the prevention of article sharing between patients and might reflect a better implementation of other hygienic precautions.…”
Section: Evidence Of Nosocomial Transmission and Preventive Strategiesmentioning
confidence: 99%
“…Some of these advances were the introduction of recombinant erythropoietin for the treatment of anemia that eliminated the need for regular blood transfusion, the routine anti-HCV screening test implemented at the blood centers preventing the transfusion route of HCV transmission, the modernization of new dialysis equipment, and the requirement of periodic anti-HCV screening of all patients undergoing hemodialysis treatment that permitted the individualization of treatment. Calabrese et al (28) and others (29) showed that by dialyzing HCV-positive patients using separate equipment in a dedicated area (but not a separate room) led to a striking reduction in the incidence of HCV infection.…”
Section: Lk Silva Et Almentioning
confidence: 99%